2013
DOI: 10.1039/c3cc38369e
|View full text |Cite
|
Sign up to set email alerts
|

Controlled branching of polyglycidol and formation of protein–glycidol bioconjugates via a graft-from approach with “PEG-like” arms

Abstract: The control of the branching in polyglycidols as semibranched alternatives to traditional polyglycidols is presented. The relative abundance of dendritic carbons is lowered by five-fold compared to hyperbranched polyglycidols. It is the first example of tailoring the branching in polyglycidol and creating protein-glycidol bioconjugates as alternatives to pegylated biostructures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 17 publications
1
39
1
2
Order By: Relevance
“…, ▪) with temperature was observed for P[(VA) ‐g‐ (hPG)] (Table S4). This is in contrast to the work on the synthesis of a hPG homopolymer carried out by Harth and coworkers which displayed a temperature dependence . The difference in temperature dependence could be attributed to their smaller initiator (isoamyl alcohol), different catalyst (tin[II] trifluoromethanesulfonate), or the short chain lengths of the grafted hPG chains in P[(VA) ‐g‐ (hPG)] prepared here were insufficient for this trend to be observed.…”
Section: Resultscontrasting
confidence: 95%
See 1 more Smart Citation
“…, ▪) with temperature was observed for P[(VA) ‐g‐ (hPG)] (Table S4). This is in contrast to the work on the synthesis of a hPG homopolymer carried out by Harth and coworkers which displayed a temperature dependence . The difference in temperature dependence could be attributed to their smaller initiator (isoamyl alcohol), different catalyst (tin[II] trifluoromethanesulfonate), or the short chain lengths of the grafted hPG chains in P[(VA) ‐g‐ (hPG)] prepared here were insufficient for this trend to be observed.…”
Section: Resultscontrasting
confidence: 95%
“…The hyperbranched structure results in increased hydroxyl functionality and therefore polymers with greater %DB will have greater hydroxyl content. Harth and coworkers polymerized glycidol using isoamyl alcohol as the initiator and tin octoate as the catalyst and have shown that temperature can affect the %DB of hPG, as the %DB decreased from 24% at 40 °C to 15% at −15 °C …”
Section: Introductionmentioning
confidence: 99%
“…A conjugate with midfunctional PG demonstrated significantly higher activity than its linear counterpart at a similar MW [26]. Harth and coworkers were the first to demonstrate in situ grafting of branched PG from Bovine Serum Albumin (BSA) using Ring Opening Polymerization (ROP) with the ability to control the degree of branching [28]. …”
Section: Non-degradable Peg Alternativesmentioning
confidence: 99%
“…The graft polymerization of GL from SiO 2 NP-PCL-OH (prepared in Section 2.3) using tin triflate was performed by modifying the method reported in the literature [26]. SiO 2 NP-PCL-OH (500 mg) was dispersed by sonication in 25 mL of anhydrous anisole in a 100 mL Schlenk flask.…”
Section: Sirop Of Gl From the Pcl Grafted Silica Nanoparticles (Sio 2mentioning
confidence: 99%